CEO Appointments and the Loss of Firm-specific Knowledge - Putting Integrity Back into Hiring Decisions - Katja Rost; Soren Salomo; Margit Osterloh (Center for Research in Economics, Management and the Arts (CREMA), 2008)
A rarely studied trend in corporate governance is the increasing tendency to fill CEO openings through external hires rather than through internal promotions: Kevin J. Murphy and Ján Zábojník (2004) show that the proportion of outside hires has doubled and their pay premium almost quadrupled over the last thirty years. Assuming that general managerial skills are becoming more important relative to firm-specific skills, the authors conclude that competition in the managerial labor market establishes optimal contracts. In our model and our empirical analysis we question this explanation by assuming that over the past decades the dishonesty of the predecessor has become relatively more important for the appointment decisions of firms. We conclude that outside hires are a suboptimal trend because external candidates even step up the regression of integrity in firms: As nobody has an incentive to invest in firm-specific knowledge, not only the performance of firms drops, but also the remaining integrity.
Keywords: G34; J23; J41; M52; 330; CEO Appointments; external hires; suboptimal contracts